At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine the limit [tex]\(\lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}}\)[/tex], we need to carefully analyze the behavior of the function as [tex]\(x\)[/tex] approaches 2 from the right.
Here is a step-by-step solution:
1. Rewrite the Expression:
The given limit is:
[tex]\[ \lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}} \][/tex]
Observe that both the numerator [tex]\(x - 2\)[/tex] and the denominator [tex]\(\sqrt{x-2}\)[/tex] involve the term [tex]\(x - 2\)[/tex].
2. Simplify the Expression:
Factorize the numerator in terms of the denominator:
[tex]\[ \frac{x-2}{\sqrt{x-2}} = \frac{y}{\sqrt{y}} \quad \text{where} \quad y = x - 2 \][/tex]
As [tex]\(x \to 2^{+}\)[/tex], [tex]\(y\)[/tex] approaches 0 from the right (i.e., [tex]\(y \to 0^{+}\)[/tex]).
3. Simplify Further:
The expression [tex]\(\frac{y}{\sqrt{y}}\)[/tex] can be simplified as follows:
[tex]\[ \frac{y}{\sqrt{y}} = \frac{y}{y^{1/2}} = y^{1 - 1/2} = y^{1/2} = \sqrt{y} \][/tex]
4. Take the Limit:
Now, we take the limit of [tex]\(\sqrt{y}\)[/tex] as [tex]\(y \to 0^{+}\)[/tex]:
[tex]\[ \lim_{{y \to 0^{+}}} \sqrt{y} \][/tex]
The square root function [tex]\(\sqrt{y}\)[/tex] approaches 0 as [tex]\(y\)[/tex] approaches 0 from the right.
5. Conclusion:
Therefore, the limit is:
[tex]\[ \lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}} = \lim_{{y \to 0^{+}}} \sqrt{y} = 0 \][/tex]
So, we conclude that:
[tex]\[ \lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}} = 0 \][/tex]
Here is a step-by-step solution:
1. Rewrite the Expression:
The given limit is:
[tex]\[ \lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}} \][/tex]
Observe that both the numerator [tex]\(x - 2\)[/tex] and the denominator [tex]\(\sqrt{x-2}\)[/tex] involve the term [tex]\(x - 2\)[/tex].
2. Simplify the Expression:
Factorize the numerator in terms of the denominator:
[tex]\[ \frac{x-2}{\sqrt{x-2}} = \frac{y}{\sqrt{y}} \quad \text{where} \quad y = x - 2 \][/tex]
As [tex]\(x \to 2^{+}\)[/tex], [tex]\(y\)[/tex] approaches 0 from the right (i.e., [tex]\(y \to 0^{+}\)[/tex]).
3. Simplify Further:
The expression [tex]\(\frac{y}{\sqrt{y}}\)[/tex] can be simplified as follows:
[tex]\[ \frac{y}{\sqrt{y}} = \frac{y}{y^{1/2}} = y^{1 - 1/2} = y^{1/2} = \sqrt{y} \][/tex]
4. Take the Limit:
Now, we take the limit of [tex]\(\sqrt{y}\)[/tex] as [tex]\(y \to 0^{+}\)[/tex]:
[tex]\[ \lim_{{y \to 0^{+}}} \sqrt{y} \][/tex]
The square root function [tex]\(\sqrt{y}\)[/tex] approaches 0 as [tex]\(y\)[/tex] approaches 0 from the right.
5. Conclusion:
Therefore, the limit is:
[tex]\[ \lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}} = \lim_{{y \to 0^{+}}} \sqrt{y} = 0 \][/tex]
So, we conclude that:
[tex]\[ \lim_{{x \to 2^{+}}} \frac{x-2}{\sqrt{x-2}} = 0 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.